KAJIAN PENGEMBANGAN TEKNOPRENEURSHIP DI INDONESIA - Endang Siti Rahayu (Universitas Sebelas Maret, 2005)
Experiance many country in Asia showed that technopreneur give positive result economy development with fantastic economy rate like Taiwan, Singapore, Malaysia and many other country. This is significant condition after crisis. Because of Indonesia condition want to get out quickly from economy crisis, this country try economic community side with small-midle corporate empowerment